The readiness of FTMSK students towards the implementation of mobile learning in learning C++ programming language / Khairu Faradilla Mohd Zaini - Mohd Zaini, Khairu Faradilla (Faculty of Computer and Mathematical Sciences, 2007)
Mobile devices are gaining popularity among youngsters nowadays. Emerging mobile devices provide opportunities for new kinds of support for teaching and learning but also pose challenges. In FTMSK, there is lack of studies to investigate the readiness of the students towards the implementation of mobile learning in C++ progranmiing language. The research on educational potential of mobile devices also is lacking in FTMSK. Therefore, this paper primarily aims to determine the readiness of FTMSK students towards the implementation of mobile learning in learning C++ programming language, as well as to identify the advantages and disadvantages of mobile devices for educational purposes. The methodology that has been used to achieve the objectives of the project are through survey questionnaires and from the literature reviews. Data that has been collected and analysed showed that most of the respondents are ready to implement mobile learning in learning C++ programming language since majority of them like to learn using technology (85 %), interested to know more about mobile learning (75%) and agree if mobile learning is implemented in learning C++ programming language (90